(3TQM Ydi TQGFY GdESdGes - (3eLghds
(3ChdgG (B:s
(3HSe Gddg (B... (3cJGH Gdhbha hGdUObGJ , bhdg GdChd Gdhba (B: (3YbO KeQJg JMHjS GdCUd hEWdGb GdefaYI Edi BNQg , bdJ gh ef hba jba hbaG hhbhaG jJYOi hdG jJYOi ceG aj GdUMGM hZjQg jbGd hbaJ GdOGHI hhqbaJgG EPG GeScJgG (B...s
(3BNQgG (B:s
... (3aGdRhLI ZjQ eJdaI ddSOSjf ef GdCQHYI dYOe fahP JUQagG hEfeG gj eJdaI dSOS hGMO ef GdSOSjf GdPjf Mce HfahP JSQageG ajgeG (B.s
(3efbhd ef NW GdeUfas
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
Keywords: (3abg GdePGgH GdCNQis